Finding green in today's consumers- from consumption to conservation / Norliana Mohd Faizal - Mohd Faizal, Norliana (2008)
The purposes of this paper is to identify the level of green in today's Kota Kinabalu consumer, to identify the preparedness of their acceptance towards the green marketing also to identify whether green marketing are able to influence the consumer in Kota Kinabalu. A questionnaire was designed and answered by Kota Kinabalu Wetland Centre consumers by completing the questionnaire also through online survey. Random sampling technique was used for the research. Based on the research findings, Most of the Kota Kinabalu's consumers are ready for green marketing. Most of them also aware to green marketing. The three variables which consist of social influence, environmental attitudes and behaviours, environmental awareness and commitment influence their level of green also acceptance of the green marketing. Furthermore, the findings also identify the level of green in the consumer which is divided to 4 level which is pale green, light green, green and dark green. Based on the finding also the researcher identifies the demographic profile of the green consumer. Attitudes and behaviour of consumer towards the green products is important to identify to sustain the green marketing. Some of the consumers are aware to green marketing but some of them don't have the commitment to act to green. Future research needs to be replicate in order to sustaining the green marketing.